Management accounting and integrated information systems: How to exploit the potential for management accounting of information technology - Anders Rom (Copenhagen Business School (CBS), 2008)
A lag seems to exist between management accounting techniques and management accounting practices of organisations (Bjørnenak, 1997a). The accounting lag exists in spite of the interaction taking place between academia and practice in terms of researchers conducting field studies and management accountants attending research-based courses before and during their careers in practice.
hdl:10398/7717
Keywords: 650